Finding Open Access Publications by UWM Authors - (:unkn) unknown (My University, 2018)
This study looks at the open access publications affiliated with the University of Wisconsin, Milwaukee, in Web of Science Core Collection. Such analysis became possible based on a partnership of Clarivate Analytics and Impactstory for integrating new technology which enabled finding an individual open access article from a publisher’s website or an author self-archived manuscript from a repository into Web of Science. The study concludes with three observations: There is 17.4% open access compared to all records affiliated with UWM. There is open access citation advantage for UWM authors. There is prevalence of Gold or Bronze over Green versions at UWM.
Keywords: Web of Science; Unpaywall; UWM authors; open access; citation advantage